Does short-term gluteal activation enhance muscle performance? - Cochrane, D. J.; Harnett, M. C.; Pinfold, S. C. (Research in Sports Medicine, 2017)
A reduction in gluteus maximus (GM) strength may contribute to the etiology of musculoskeletal impairments and lower-extremity injuries. Currently, there is a paucity of evidence regarding the efficacy of implementing a short-term gluteal activation programme to improving muscle performance. Twenty four semi-professional rugby males were assigned randomly to a gluteal activation group (GLUTE) or a control group (CON). During the 6-week training intervention, the GLUTE and CON groups performed the same training, however that GLUTE group performed seven gluteal activation exercises three times weekly prior to their normal training sessions. Whilst the CON group performed the conventional training with no gluteal activation exercises. Electromyography (EMG) was measured during a maximal isometric unilateral squat (MVIC) and unilateral hip extension force from the left and right vastus lateralis, gluteus maximus, and biceps femoris. After 6 weeks of training there was no significant main or interaction effect (p > 0.05) of EMG and peak force for MVIC and hip extension between GLUTE and CON. The current gluteal activation programme did not enhance EMG activity and hip extension force therefore, the body-weight exercises may not have been sufficient to elicit the appropriate changes.